Learning Mandarin Language in Ferdinand de Saussure Descriptive Linguistic Perspective at Senior High School - Darwin, David; Zuriyati, Zuriyati; Rohman, Saifur (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to describe the learning of Mandarin from the perspective of Ferdinand de Saussure's descriptive linguistics in students of Madrasah Aliyah Ma'arif NU Lampung. The method used by researchers is a qualitative approach with phenomenological methods. The data in this study is in the form of Chinese Language learning in Madrasah Aliyah Ma'arif NU Lampung students. Data sources were obtained from students, teachers, and language tutors at Madrasah Aliyah Ma'arif NU Lampung. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis in this study used phenomenological analysis. The results of this study show that Chinese language learning has a positive impact on students. The positive impact is in the form of increasing Chinese language skills and their involvement in active and fun learning. However, some of the problems encountered in learning Chinese in Madrasah Aliyah Ma'arif NU Lampung are the introduction to Chinese characters (Hanzi) and how to write them.